Teaching and learning through critical reflective practice - Ghaye, Tony.; Ghaye, Kay. (London : D. Fulton Publishers, 1998)
Maps out the professional, political and theoretical landscape of reflective practice, its nature and purposes and the claims being made for it. The authors centre their text on a model of the teacher as a reflective learner, with enlightenment and empowerment as central themes
Includes bibliographical references and index.
Keywords: Teaching; Teachers -- Training of; Reflection (Philosophy); Experiential learning